Analysis of a two-stage ionic wind pump with multiple needle-to-mesh electrodes for cooling electronics. (25th February 2021) - Zeng, M.J.; Zhang, J.F.; Wang, S.; Qu, Z.G.
Highlights: Two groups of interactive mechanisms can affect the flow characteristics. Counter discharge between stages is discovered to induce extra power consumption. An optimized ionic wind pump layout is obtained to reduce heat sink temperature. Abstract: Ionic wind pumps have considerable potential for flow control, heat transfer, and drying applications due to their advantages of low energy consumption, compact structure, flexible design, and lack of moving parts. However, a high flow rate ionic wind pump with large cross-sectional for cooling high thermal power electronic devices requires further research. In this study, a two-stage ionic wind pump with needle-to-mesh electrodes was developed for cooling electronics. Experimental systems were established to test the flow and heat transfer characteristics. The effects of needle electrodes' arrangement, mesh electrodes' structure, needle tip-to-mesh gap, and stage distance on the output velocity and power consumption of ionic wind pumps were investigated. The influence of the arrangement of an ionic wind pump and heat sink on the cooling performance was also studied. Two groups of interactive mechanisms, interference between neighboring needles and needle density, the discharge effect and the resistance effect of mesh electrodes, affected the flow characteristics. A grid size with an optimal value of 4 mm was obtained by combining the discharge and resistance effects. As the needle tip-to-mesh gap increased, the velocity at the same applied voltage decreased but the velocity limit near the breakdown voltage increased. Counter discharge between the stages induced additional power consumption. As the stage distance increased, the breakdown shifted from between two stages to within each stage. The counter discharge disappeared as the stage distance increased to greater than 29 mm. At the ionic wind pump's optimum parameters, the output velocity of 3.91 m/s was achieved. And the cooling experiment indicated that the optimized ionic wind pump can reduced the surface temperature of a 200 W power heat source by more than 30 °C. The present study provides guidance for heat dissipation designs for maintenance-free electronics in remote areas.